Adsorptive Stripping Voltammetry of Nickel with 1-Nitroso-2-Napthol Using a Bismuth Film Electrode - Segura-Segura, R; Segura-Segura, R; Godoy-Gonzalez, F; Godoy-Gonzalez, F (2011)
A sensitive procedure is presented for the voltammetric determination of nickel. The procedure involves an adsorptive accumulation of nickel 1-nitroso-2-napthol (NN) complex on a bismuth film electrode prepared ex situ by electrodeposition. The most suitable operating conditions and parameters such as pH, ligand concentration (CNN), adsorptive potential (E ads), adsorptive time (tads), scan rate and others were selected and the determination of nickel in aqueous solutions using the standard addition method was possible. The adsorbed Ni-NN complex gives a well defined cathodic stripping peak current at -0.70 V, which was used for the determination of nickel in the concentration range of 10.0-70.0 ?g L-1 (pH 7.5; CNN 6.5 ?mol L-1; Eads -0.30 V; t ads 60 s) with a detection limit of 0.1 ?g L-1. The relative standard deviation for a solution containing 10.0 ?g L-1 of Ni(II) was 3.5% (n = 4). The proposed method was validated determining Ni(II) in certified reference waste water (SPS-WW1) and Certified Reference Water for Trace Elements (TMDA 51.3) with satisfactory results. Then lake water samples were analyzed. © 2011 Published by Elsevier B.V.